Flexural strength of concrete prism strengthened using CFRP with modified mortar - Radzuan, Nurshafiqah; Ali, Noorwirdawati; Abdul Hamid, Noor Azlina; Salleh, Norhafizah (Penerbit UTHM, 2020)
Reinforced concrete (RC) is a good durable material that commonly used in construction compared to others. However, reinforced concrete structures may be damaged and are suffering from various deteriorations because of overloading and an inadequacy of design which may be attributed to cracks, spalling, large deflection, and more. Hence, it is essential to find repair and strengthening techniques of deteriorated concrete structures not only suitable in terms of the economy, but also to use them for their intended service life.